Molecular Analysis of Isoniazid-Resistant Mycobacterium tuberculosis Isolates from England and Wales Reveals the Phylogenetic Significance of the ahpC −46A Polymorphism - Baker, L. V.; Brown, T. J.; Maxwell, O.; Gibson, A. L.; Fang, Z.; Yates, M. D.; Drobniewski, F. A. (Antimicrobial Agents and Chemotherapy, 2005)
Classifications Services AAC Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue AAC About AAC Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy AAC RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0066-4804 Online ISSN: 1098-6596 Copyright © 2014 by the American Society for Microbiology. For an alternate route to AAC .asm.org, visit: AAC